Ganoderma lucidum polysaccharides attenuates pressure-overload-induced pathological cardiac hypertrophy - Zhen, Changlin; Wu, Xunxun; Zhang, Jing; Liu, Dan; Li, Guoli; Yan, Yongbo; He, Xiuzhen; Miao, Jiawei; Song, Hongxia; Yan, Yifan; Zhang, Yonghui (Frontiers in Pharmacology, 2023)
Pathological cardiac hypertrophy is an important risk factor for cardiovascular disease. However, drug therapies that can reverse the maladaptive process and restore heart function are limited. Ganoderma lucidum polysaccharides (GLPs) are one of the main active components of Ganoderma lucidum (G. lucidum), and they have various pharmacological effects. GLPs have been used as Chi-nese medicine prescriptions for clinical treatment. In this study, cardiac hypertrophy was induced by transverse aortic constriction (TAC) in mice. We found that GLPs ameliorate Ang II-induced cardi-omyocyte hypertrophy in vitro and attenuate pressure overload–induced cardiac hypertrophy in vivo. Further research indicated that GLPs attenuated the mRNA levels of hypertrophic and fibrotic mark-ers to inhibit cardiac hypertrophy through the PPARγ/PGC-1α pathway. Overall, these results indi-cate that GLPs inhibit cardiac hypertrophy through downregulating key genes for hypertrophy and fibrosis and attenuate pressure overload-induced pathological cardiac hypertrophy by activating PPARγ. This study provides important theoretical support for the potential of using GLPs to treat pathological myocardial hypertrophy and heart failure.